Faster Traveling Atmosphere Disturbances Caused by Polar Ionosphere Turbulence Heating. Issue 3 (9th March 2018) - Liu, Jing; Wang, Wenbin; Burns, Alan; Oppenheim, Meers; Dimant, Yakov
Abstract: A new module, which includes both the turbulence electron heating and the electron‐neutral cooling rate correction associated with the Farley‐Buneman onstability (FBI) in the National Center for Atmospheric Research‐Thermosphere Ionosphere Electrodynamics Global Circulation Model, enables us, for the first time, to investigate the intimate coupling between polar turbulence electron heating and thermosphere disturbances in the context of a first‐principle, self‐consistent model. Our simulation results show that during geomagnetic storms, after taking the FBI effects into account, Joule heating is almost doubled in the E region at these locations of strong convection electric field. This increases ( 6%) the phase speed of traveling atmosphere disturbances at around 400 km that are launched from both hemispheres. Additional heating sources also directly produce a divergence in the zonal wind with magnitudes of 20 m/s in the lower thermosphere. However, the FBI impact on the thermosphere at F region altitudes is not so straightforward. E region anomalous electron heating in association with the FBI can change the phase speeds and magnitudes of traveling atmosphere disturbances from high latitudes in both hemispheres and consequently modify global neutral wind circulation at F region altitudes. This, in turn, can affect the neutral temperature through adiabatic compressional heating and expansive cooling by about 40 K. This study demonstrates how the ionosphere‐thermosphere physical processes across different temporal and spatial scales are tightly coupled together throughout the whole upper atmosphere domain. Key Points: The study aimed to investigate the intimate coupling between polar turbulence electron heating and thermosphere disturbances Anomalous electron heating accelerates thermospheric TADs Ionosphere‐thermosphere physical processes across different temporal and spatial scales are tightly coupled